Structural basis for PAS domain heterodimerization in the basic helix–loop–helix-PAS transcription factor hypoxia-inducible factor - Erbel, Paul J. A. (National Academy of Sciences, 2003)
Biological responses to oxygen availability play important roles in development, physiological homeostasis, and many disease processes. In mammalian cells, this adaptation is mediated in part by a conserved pathway centered on the hypoxia-inducible factor (HIF). HIF is a heterodimeric protein complex composed of two members of the basic helix–loop–helix Per-ARNT-Sim (PAS) (ARNT, aryl hydrocarbon receptor nuclear translocator) domain family of transcriptional activators, HIFα and ARNT. Although this complex involves protein–protein interactions mediated by basic helix–loop–helix and PAS domains in both proteins, the role played by the PAS domains is poorly understood. To address this issue, we have studied the structure and interactions of the C-terminal PAS domain of human HIF-2α by NMR spectroscopy. We demonstrate that HIF-2α PAS-B binds the analogous ARNT domain in vitro, showing that residues involved in this interaction are located on the solvent-exposed side of the HIF-2α central β-sheet. Mutating residues at this surface not only disrupts the interaction between isolated PAS domains in vitro but also interferes with the ability of full-length HIF to respond to hypoxia in living cells. Extending our findings to other PAS domains, we find that this β-sheet interface is widely used for both intra- and intermolecular interactions, suggesting a basis of specificity and regulation of many types of PAS-containing signaling proteins.